Preconcentration and Determination of Iron, Nickel, Lead and Zinc after Solid Phase Extraction using 5-Aphen Functionalized poly(GMA-MMA-DVB) Microspheres - Alpdogan, Guzin; Yamak, Hale Berber; Zor, Sule Dinc; Elmali, Fikriye Tuncel (BENTHAM SCIENCE PUBL LTD, 2016)
Background: Polymer based adsorbents and their modified forms by various ligands have been effectively used for separation, preconcentration, determination and removal of heavy metal ions from different matrices. This paper proposes a solid phase extraction method based on 5-amino-1,10-phenanthroline (5-Aphen) functionalized glycidyl methacrylate-methyl methacrylate-divinylbenzene (GMA-MMA-DVB) crosslinked-polymeric microspheres for the determination of Fe (II), Ni (II), Pb (II) and Zn (II) in herbal tea samples employing flame atomic absorption spectrometry (FAAS). Methods: The prepared adsorbent was characterized by FT-IR spectroscopy and BET. Several experimental variables affecting the sensitivity and efficiency of SPE method for the metal ions studied were investigated in detail by FAAS. Results: The optimal values of the adsorbent amount, pH, eluent properties, and flow rates were determined. The preconcentration factor and detection limits of the proposed SPE method and the maximum capacity of the adsorbent were found. The validity of the method was verified by the analysis of certified reference material. The developed method was successfully applied to herbal tea samples for the simultaneous preconcentration of Fe (II), Ni (II), Pb (II) and Zn (II) ions. Conclusion: The SPE method based on 5-Aphen functionalized GMA-MMA-DVB for some trace metal ions in herbal tea samples is simple, accurate, fast, low cost, high preconcentration factor and environmentally friendly. This method can also be employed to evaluate the possible risk associated with heavy metal-contaminated foods.
Keywords: 5-Aphen; glycidylmethacrylate copolymer; solid phase extraction; trace metal determination; FAAS; herbal tea; ATOMIC-ABSORPTION-SPECTROMETRY; TRACE-METAL IONS; XAD-16 CHELATING RESIN; CLOUD POINT EXTRACTION; WATER SAMPLES; HEAVY-METALS; ENVIRONMENTAL-SAMPLES; EMISSION-SPECTROMETRY; MODIFIED ELECTRODES; BIOLOGICAL SAMPLES; Chemistry